Kajian Peran Guru dalam Implementasi P5 untuk Membangun Nasionalisme Siswa Sekolah Dasar - Fatikhin, Ahmad; Agustin, Merlina; Faizah, Vina Auliatul; Setiyoko, Didik Tri (Peneliti.net, 2025)
This article examines the role of teachers in implementing the Strengthening Pancasila Student Profile (P5) Project to build nationalism in elementary school students. Using a literature review approach, this article explores how P5 can be used as a tool to introduce and strengthen Pancasila values, with a focus on developing student nationalism. P5, which is based on a project-based learning approach, allows students to learn through direct experiences related to national and social issues. The teacher, as the main facilitator, plays a key role in designing, guiding and directing students to internalize the values of Pancasila in everyday life. Apart from that, teachers also act as role models who can shape students' nationalist attitudes through exemplary implementation of Pancasila values. Even though chalenges in implementing P5 such as limited resources and understanding of the curriculum still exist, this article emphasizes the important role of teachers in building nationalist character based on love of the homeland and nationality. The results of this study show that implementing P5 at the elementary school level can be a strate-gic step in forming a generation that is not only academically intelligent, but also has a high national spirit.